1997
DOI: 10.1002/mrm.1910370108
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of solutes in agarose and alginate gels: 1H and 23Na PFGSE and 23Na TQF NMR studies

Abstract: Cells immobilized in gels experience potential metabolic restrictions in the form of reduced diffusion rates of metabolites and ions and their possible selective adsorption on the gel matrix. Diffusion and relaxation characteristics of common solutes in agarose and barium alginate gels were investigated at 37 degrees C by using 1H PFGSE and 23Na TQF NMR spectroscopy. Glucose, glycine, alanine, lactate, sodium ions, and HDO were studied. There were no selective interactions between any of the metabolites and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…In previous computational studies, concentration profiles within constructs have been computed on the basis of values in the surrounding medium (10,(21)(22)(23)(24). Except in the study by Malda (22), computed solute concentration profiles have not been confirmed by direct experimental measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous computational studies, concentration profiles within constructs have been computed on the basis of values in the surrounding medium (10,(21)(22)(23)(24). Except in the study by Malda (22), computed solute concentration profiles have not been confirmed by direct experimental measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Also the fluid flow in combination with oxygen mass transfer to and within TE constructs has been modeled in a concentric cylinder bioreactor (12). At the construct level nutrient diffusion, oxygen uptake, matrix biosynthesis, and cell growth within TE cartilage constructs have been modeled (10,(21)(22)(23)(24). The largest source of uncertainty in modeling studies, however, is associated with the cell behavior, both qualitatively and quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion-based techniques can separate the sodium signal from the intra-cellular and extra-cellular compartments based on the differences between the motional properties of the ions in these two compartments [78–80]. The fast relaxation rates and the low gyromagnetic ratio of sodium require the use of very large magnetic field gradients and fast switching, which is challenging but not impossible in clinical MRI scanners.…”
Section: Pulse Sequences For Compartment and Fluid Suppressionmentioning
confidence: 99%
“…This biexponential relaxation behavior allows the creation and detection of multiple quantum coherences (9,10). MQF NMR spectroscopy of quadrupolar I Ï­ 3 2 alkali metal nuclei has been studied extensively in macromolecular model systems (11)(12)(13)(14)(15) and in perfused organs, such as rat salivary glands (16), rat and guinea-pig hearts (17)(18)(19)(20)(21)(22), and rat liver (23). It was also applied to in vivo organs, such as rat liver (24), human brain, and skeletal muscle (25).…”
Section: Introductionmentioning
confidence: 99%